1977
DOI: 10.1042/bj1630543
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the association of yeast phosphoglycerate mutase (EC2.7.5.3) with that of haemoglobin. An ultracentrifuge study

Abstract: 1. Previous work showed that yeast phosphoglycerate mutase (EC 2.7.5.3) has a mol.wt. of between 107000 and 110000. Preliminary examination showed that at dilutions less than 0.1 g/1 the enzyme dissociated into its subunits. 2. This dissociation was quantitatively examined by both equilibrium and velocity centrifugation. 3. The mathematical analysis of the equilibrium records was tested against oxyhaemoglobin in a variety of ionic strengths and at two temperatures. 4. The estimated L2,4 (interaction coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Substantiation for this suggestion comes from two other lines of evidence. Spragg et al (1977) have shown that yeast phosphoglycerate mutase dissociates and is active in dilute solution; muscle and plant phosphoglycerate mutases are isolated as dimers and to to "3…”
Section: (Ii) Microheterogeneitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantiation for this suggestion comes from two other lines of evidence. Spragg et al (1977) have shown that yeast phosphoglycerate mutase dissociates and is active in dilute solution; muscle and plant phosphoglycerate mutases are isolated as dimers and to to "3…”
Section: (Ii) Microheterogeneitiesmentioning
confidence: 99%
“…Monophosphoglycerate mutase is the glycolytic enzyme th at catalyses the inter conversion of 3-and 2-phosphoglycerates; 2,3-diphosphoglycerate is required to prime the reaction. The enzyme isolated from yeast is a tetramer with four apparently identical subunits (Campbell et al 1974), each with a relative molecular mass of approximately 28000 as determined by physical methods (Rodwell et al 1956;Sasaki et al 1970;Fothergill & Hodgson 1976;Spragg et al 1977). X-ray crystallographic studies have been carried out to 2.8 A (0.28 nm) resolution (Winn et al 1977(Winn et al , 1982, and the determination of the amino acid sequence now permits a detailed interpretation of the structure in molecular terms.…”
Section: Introductionmentioning
confidence: 99%
“…5 , 1972), oxyhaemoglobin (Kellett, 1971), glyceraldehyde 3-phosphate dehydrogenase (Osborne & Holloway, 1974) and pyruvate kinase (Cardenas et al, 1977;Cottam et al, 1969) exist as stable dimers; the two subunits are considered to be held together by the more extensive subunit interactions where this is known. With lactate dehydrogenase (Hermann et al, 1979), dimers can only be detected as short-lived intermediates during the reassociation process; for prealbumin (Nilsson et al, 1975) and yeast phosphoglycerate mutase (Spragg et al, 1977) dimers were not detected during dissociation. Fig.…”
Section: Resultsmentioning
confidence: 97%